Widzieć malarstwo. Edukacyjne aspekty twórczości Stefana Gierowskiego = See painting. Educational aspects of the art of Stefan Gierowski - Zawada, Ernest (Kraków ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Aesthetic education is one of the important factors forming the personality of man, functioning in the world of nature and culture at the same time. The task of upbringing in this area concerns primarily the development of sensitivity to art and beauty, especially of young people. This concept, also understood as education through art, can be realized in active and passive forms.
Keywords: edukacja; kreatywność; malarstwo; kultura; education; creativity; painting; culture